Efeitos do peróxido de hidrogênio sobre a germinação e na aclimatação de plantas de milho à salinidade - Gondim, Franklin Aragão (2008)
The aim of this work was to evaluate the effects of the hydrogen peroxide (H2O2) on germination and acclimation of maize plants subject to the saline stress, in order to better understand the physiological and biochemical mechanisms involved. In the three experiments the triple hybrid of maize (Zea mays L) BRS 3003 was used. In the first experiment, the effects of H2O2 on germination of the maize seeds were evaluated; in the second, the effects of pre-treating by soaking maize seeds in H2O2 solution on the activities of antioxidative enzymes and isoenzymes; and as, the effects of the pre-treatment of maize seeds with H2O2 on acclimation of the plants to salinity and the possible mechanisms involved with this process. In the first experiment, which was carried out in a growth room, H2O2 accelerated the germination rate of maize seeds at 100 mM, but, not at 500 mM. In the second experiment, also carried out in growth room, it was observed that the pre-treatment of the seeds induced a pronounced increase in the activities of the enzymes ascorbate peroxidase (APX) and catalase (CAT), after 30 h of soaking in H2O2. It was also observed that the activity of the Guaiacol peroxidase (GPX) was smaller in the seeds soaked in H2O2 for 12, 24, 30, 36 and 42 h, in relation to those soaked in distilled water (control). However, H2O2 treatment for 48 h showed no significant differences as compared with control. The superoxide dismutase (SOD) activity was not affected by the pre-treatment of the seeds, except for the 24 h treatment. In the seeds, it was detected only one isoform of CAT and six of SOD. The pre-treatment of the seeds did not cause great changes in those isoforms, except for the intensity of the band of activity of CAT visualized in the polyacrylamide gel, which was very superior to that of the control, when the seeds were soaked by 36 and 48 h with H2O2. The increases in the activities of APX and, especially, of CAT, could be associated with the acceleration of the germination process. In the third experiment, which was carried out initially at growth room and, later, at the glasshouse, maize seeds were pre-treated for 36 h by soaking in solution of H2O2 100 mM or in distilled water. Those seeds were germinated on filter paper moistened with nutrient solution in the presence or absence of NaCl 80 mM, in a growth room. After six days, the seedling were transferred to the glasshouse and cultivated in trays containing only nutrient solution (control treatment) or nutrient solution with NaCl at 80 mM. Plants were harvest with 6, 11 and 16 days old. The results showed the pre-treatment of the seeds with H2O2 induced acclimation of the plants to the salinity. It decreased the deleterious effects of salt stress on the growth (biomass production and leaf area) of maize. This fact was associated with a higher efficiency of the antioxidative system of plants pre-treated with H2O2. CAT was the most important among the H2O2 scavenging enzymes in leaves, but, its activity was strongly reduced by salinity in plants 6 and 11 days old, however, this effect was totally reverted in the stressed plants originated from seeds pre-treated with H2O2. On the other hand, in the roots of plants submitted to saline stress, the activity of SOD was stimulated by the pre-treatment of the seeds with H2O2, in the three periods of harvest. In general, salinity reduced the photosynthetic parameters (stomatal conductance, net CO2 assimilation rate, transpiration and intracellular CO2 concentration) and the H2O2 pre-treatment of seeds was not capable to revert that effect. In terms of osmotic adjustment, the contents of organic solutes were not positively correlated to the process of acclimation to salt stress of the plants pre-treated with H2O2 to the salinity. However, the smallest values of the Na+/K+ ratio in roots and in leaves were found for the pre-treated plants submitted to salinity, when compared to those originated from of seeds pre-treated with water (control) and submitted to that same treatment, and it may also be a responsible factor for the acclimation of the maize plants to the salinity.